Realism as a third film practice - Birger Langkjær (MedieKultur: Journal of Media and Communication Research, 2011)
The concept of realism may owe much of its success to its vague definition. This article suggests that it can be useful as a term that covers a central, mainstream film practice in European and other national cinemas, located somewhere in between genre films and art films. The concept refers to a serious kind of film that does not obey classical genre rules, but nevertheless tells its stories in an accessible and often engaging form that, generally speaking, creates a more popular (yet serious) film than the art film. As a film practice, it cuts across well known but often vaguely defined sub-categories, such as social realism and psychological realism. Finally, it is argued that the dichotomy between Hollywood genre films and European art cinema ignores both national variants of basic genres and a tradition of realism as a mainstream film practice.